STRATEGI GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV SD ISLAM SE-KECAMATAN SUNGAI AMBAWANG - Triyanti, Tiya; Yusriadi, Yusriadi; Setyaningrum, Saumi (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2023)
The purpose of this study is to find out: what strategies are used, step for implementing learning strategies used by teachers in increasing students' learning motivation to achieve KKM scores for Indonesian subjects and obstacles faced by teachers and their solutions in implementing learning strategies. This research includes qualitative research in the form of descriptive research. This research can be concluded that: (1) media-assisted strategies, storytelling methods, inquiry, contextual, problem-based, cooperative, expository, participatory, with modules, complete learning. (2) conveying goals and motivating students, informing, organizing students into study groups, guiding groups for work and study, evaluation. (3) a. Obstacles in implementing learning strategies are: difficult material that is not in accordance with students' initial knowledge, students lack confidence in expressing opinions, difficulty managing time allocation, choosing appropriate strategies, not wanting to listen to teacher explanations or busy themselves. b. How to overcome obstacles in motivating students such as: by taking a personal approach to students, providing freedom of opinion, providing motivations that can help students to be more confident and enthusiastic about learning, not forcing students to learn, providing a little entertainment so that children do not bored and rewarded.